Analisis Tingkat Inflasi di Indonesia Menggunakan Teknologi Big Data Analytics - Silitonga, Lidya Elisabet Theogracia; Hendra Suputra, I Putu Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 2 (2023): JELIKU Volume 12 No 2, November 2023, 2023)
Inflation is a state of the country's economy where there is a tendency to increase the price of goods and services within a certain period of time. In general, inflation in Indonesia occurs due to pressure from the demand side (Demand Pull Inflation) and from the supply side (Cost Push Inflation). From the demand side, according to monetary theory, this excess demand is caused by too much money circulating in the community, while the amount of goods in the market is small. From the supply side (Cost Push Inflation), inflation is caused by an increase in production costs. Unstable inflation has a negative impact Therefore, inflation control is very important. In this study, the inflation rate in Indonesia will be carried out which aims to determine the development and control of inflation in Indonesia. This study will use secondary data from the Central Statistics Agency (BPS). The research method that will be used is the big data analytics method. In this study, the author uses the Tableau tool to visualize data on Indonesian inflation data taken from the Central Statistics Agency (BPS).